Cognitive general imagery: The forgotten imagery function? - Westlund, N.; Pope, J. P.; Tobin, D. (Journal of Imagery Research in Sport and Physical Activity, 2012)
It is well known that athletes use mental imagery for five different functions; motivational general-arousal (MG-A; arousal and stress) motivational general-mastery (MG-M; control, mental toughness, and self-confidence), motivational specific (MS; goal-oriented responses), cognitive general (CG; sport-specific strategies), and cognitive specific (CS; sport-specific skills; Hall et al., 1998; Paivio, 1985). While much research has been conducted on the MG-A, MG-M, MS, and CS imagery functions, there has not been as much focus on CG imagery. This is somewhat disheartening since various researchers have pointed out this issue many times (e.g., Hall, 2001). The purpose of this review was to examine the research conducted on CG imagery since the publication of Martin and colleagues` (1999) applied model of imagery use. A literature search was conducted of published peer-reviewed journal articles using Proquest to identify all studies that have examined CG imagery. Forty-three articles were identified as relevant towards understanding the role of CG imagery in sport. The research findings were discussed in one of two sections depending on the type of study design used (e.g., descriptive/correlational study or imagery intervention). The strengths and weaknesses of the CG imagery studies are discussed. From this review, the authors hope to make researchers aware of the avenues that still need to be explored in regards to CG imagery, as well as provide researchers with potential approaches to answer such questions.